2010
DOI: 10.1038/nrendo.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

SPARC: a key player in the pathologies associated with obesity and diabetes

Abstract: SPARC (secreted protein acidic and rich in cysteine, also known as osteonectin or BM-40) is a widely expressed profibrotic protein with pleiotropic roles, which have been studied in a variety of conditions. Notably, SPARC is linked to human obesity; SPARC derived from adipose tissue is associated with insulin resistance and secretion of SPARC by adipose tissue is increased by insulin and the adipokine leptin. Furthermore, SPARC is associated with diabetes complications such as diabetic retinopathy and nephropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 108 publications
3
129
0
Order By: Relevance
“…Furthermore, SPARC levels were found to correlate positively with BMI, FAT%, TG, f-INS, 2hINS, and HOMA IR in simple regression analysis, and multiple regression analysis showed that TG and HOMA IR were independently correlated with plasma SPARC levels. As shown in the literature, SPARC has been shown to inhibit the differentiation of preadipocytes to mature adipocytes, and to increase adipose tissue fibrosis (15,16). Thus, SPARC could inhibit the expansion of subcutaneous abdominal adipose tissue (6), reduce the ability of adipose tissue to store TGs, and increase the TGs in the circulation and lipid infiltration of other organs resulting in IR.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, SPARC levels were found to correlate positively with BMI, FAT%, TG, f-INS, 2hINS, and HOMA IR in simple regression analysis, and multiple regression analysis showed that TG and HOMA IR were independently correlated with plasma SPARC levels. As shown in the literature, SPARC has been shown to inhibit the differentiation of preadipocytes to mature adipocytes, and to increase adipose tissue fibrosis (15,16). Thus, SPARC could inhibit the expansion of subcutaneous abdominal adipose tissue (6), reduce the ability of adipose tissue to store TGs, and increase the TGs in the circulation and lipid infiltration of other organs resulting in IR.…”
Section: Discussionmentioning
confidence: 94%
“…The matricellular glycoprotein termed secreted protein acidic and rich in cysteine (SPARC) has a key role in extracellular matrix (ECM) assembly and molding. Consistently, SPARC has been implicated in the pathogenesis of several fibrotic disorders, such as adipose tissue fibrosis, 1 hepatic fibrosis, 2,3 lung fibrosis, 4 and scleroderma. 5 This notion comes from data generated in Sparc Ϫ/Ϫ mice or gene-silencing strategies in models of skin, liver, and pulmonary fibrosis.…”
mentioning
confidence: 99%
“…In fact, osteonectin is associated with diabetes complications such as diabetic retinopathy and nephropathy, conditions that are ameliorated in the SPARC-knockout mouse model and, as a regulator of the extracellular matrix, osteonectin also contributes to adipose-tissue fibrosis. [18]. Regarding tumors, osteonectin modulate the interaction between tumor cells and the normal surrounding cells, affecting proliferation, survival and migration of cancer cells, tumor invasion, and metastasis [7].…”
Section: Introductionmentioning
confidence: 99%